INTENSITAS PENGGUNAAN MEDIA SOSIAL DAN PERSEPSI REMAJA TENTANG CITRA TUBUH IDEAL - Roudhatul Khasanah, Laely Alfiani; Cahyaningrum, Etika Dewi; Wirakhmi, Ikit Netra (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
The intensity of social media (Instagram) usage is how long and how often someone accesses it. The duration of accessing Instagram often triggers perceptions about ideal body image in society. The purpose of this study to analyze the effect of the intensity of Instagram social media usage on adolescents' perceptions about ideal body image at SMA Negeri 4 Purwokerto. The research method used is a non-experimental quantitative research type with a cross-sectional approach. The sample consisted of 124 students. The research instruments included a questionnaire that measured the intensity of Instagram usage using a scale adapted from previous researchers and the perception of ideal body image using the Multidimensional Body Self-Relations Questionnaire (MBSRQ) measuring instrument. The test results using SPSS version 25, the characteristics of the respondents were mostly female (72.6%), the intensity of Instagram usage and adolescents' perceptions about body image were in the moderate category, 73.4% and 60.5%, respectively. The results of the Spearman rank test showed a p value of 0.004 (<0.05) so that H1 was accepted and H2 was rejected. Thus, there is an influence between the intensity of Instagram use and ideal body image with a significance value of 0.004 <0.05, so it can be concluded that the two variables are correlated with a correlation coefficient value of 0.259, which means that the level of relationship between the two variables is in a very weak relationship.